Wages, productivity and aging - Benoît Dostie (Institute for the Study of Labor (IZA), 2006)
In this article, we estimate age based wage and productivity differentials using linked employer-employee Canadian data from the Workplace and Employee Survey 1999-2003. Data on the firm side is used to estimate production functions taking into account the age profile of the firm's workforce. Data on the workers' side is used to estimate wage equations that also depend on age. Results show concave age-wage and age-productivity profiles. Wage-productivity comparisons show that the productivity of workers aged 55 and more with at least an undergraduate degree is lower than their wages. For other groups, we find that wages do not deviate significantly from productivity estimates.
urn:nbn:de:101:1-20080509186
Keywords: 330